Associated Gas Monetization via miniGTL : Conversion of Flared Gas into Liquid Fuels and Chemicals, Report III - Fleisch, Theo H. (World Bank, Washington, DC, 2016)
Associated gas monetization via mini gas to liquids (GTL) is the third in a series of reports, starting in February 2012, that describe technologies for the conversion of small volumes (in the range 1 to 20 million standard cubic feet per day or about 10 to 200 million cubic meters per annum) of gas into liquid fuels and chemicals. The technologies are very applicable for utilization of gas currently being flared. The reports describe the various technologies currently available, the companies offering these technologies to the market, and assessments of the readiness of each technology for commercial application. The latest report (No. III) finds a number of technologies are now being applied commercially, with even more ready to take that step.